Value chain management strategy of sugar cane in Takalar sugar factory - Sumarata, De Naddya YF; Rusman, Muhammad; Parenreng, Syarifuddin M. (Journal Industrial Servicess, 2023)
The primary and supporting activities of the Takalar Sugar Factory have been hindered by limited resources, resulting in low productivity. This research aims to determine strategies to enhance productivity effectively by adding value. It involves analyzing relationships among stakeholders using a Value Chain Analysis for internal activities and a PESTLE Analysis for external environmental factors. A TOWS Analysis is then formed, considering threats, opportunities, weaknesses, and strengths. This process helps develop a prioritized management strategy plan through the Analytical Hierarchy Process (AHP). The sugarcane commodity chain comprises production flows, price information in the supply chain, and income streams involving four key actors: farmers, producers, traders, and end consumers. This analysis reveals suboptimal service activities and production technology. Moreover, low bidding prices contribute to uneven income distribution. Additionally, existing policies aimed at empowering sugarcane farmers result in low-value creation. Consequently, the proposed priority strategies for management revolve around enhancing efficiency in sugarcane production, leveraging modern cultivation techniques, employing Internet of Things technology, increasing sugarcane production capacity through on-farm restructuring, revitalizing off-farm factories for sugar production, and expanding market share by promoting new packaging products.